'A word from another world': mourning and similes in Homeric epic and Alice Oswald's Memorial. (9th February 2018) - Pache, Corinne
Abstract: This article focuses on Alice Oswald's 2012 Memorial: A Version of Homer's Iliad and its connections with ancient epic and lament. Oswald's poem is inspired by the Iliad, but omits the plot and most of the main events to focus on minor characters' encounters with death and the grief they leave behind. Memorial thus strongly rejects the possibility of heroism on the battlefield, and foregrounds mourning. Oswald's narrator interacts with both the characters of the poem and the audience, reactivating an ancient tradition for a modern audience, turning readers (and listeners) into mourners, and connecting the dead from the past and the audience in the present.